Cancer Clocks Out for Lunch: Disruption of Circadian Rhythm and Metabolic Oscillation in Cancer - Altman, Brian J. (Frontiers in Cell and Developmental Biology, 2016)
Circadian rhythms are 24-hour oscillations present in most eukaryotes and many prokaryotes that synchronize activity to the day-night cycle. They are an essential feature of organismal and cell physiology that coordinate many of the metabolic, biosynthetic, and signal transduction pathways studied in biology. The molecular mechanism of circadian rhythm is controlled both by signal transduction and gene transcription as well as by metabolic feedback. The role of circadian rhythm in cancer cell development and survival is still not well understood, but as will be discussed in this review, accumulated research suggests that circadian rhythm may be altered or disrupted in many human cancers downstream of common oncogenic alterations. Thus, a complete understanding of the genetic and metabolic alterations in cancer must take potential circadian rhythm perturbations into account, as this disruption itself will influence how gene expression and metabolism are altered in the cancer cell compared to its non-transformed neighbor. It will be important to better understand these circadian changes in both normal and cancer cell physiology to potentially design treatment modalities to exploit this insight.